The Metabolic Role of the Microbiome: Implications for NAFLD and the Metabolic Syndrome - Quigley, Eamonn M. M.; Abu-Shanab, Ahmed; Murphy, Eileen F.; Stanton, Catherine; Monsour, Howard P., Jr. (Seminars in Liver Disease, 2016)
Nonalcoholic fatty liver disease (NAFLD) has rapidly emerged as one of the most prevalent liver diseases worldwide and is set to achieve virtually epidemic proportions if current trends in obesity continue. A considerable volume of data from animal experiments has revealed the magnitude of the metabolic contribution of the gut microbiome and how a disordered microbial population could contribute to the development of obesity and its complications, including NAFLD. Although considerable progress has been made in developing a role for the microbiome in NAFLD and nonalcoholic steatosis (NASH), there are still many issues to be resolved, including the nature and location of the altered microbiome (i.e., small intestine or colon, or both); the specificity of deficits in intestinal integrity to NAFLD/NASH versus liver disease in general; the metabolic pathways, in man, that are key to the influence of the microbiome; and finally, the therapeutic interventions that are likely to be of benefit to our patients.As always, the situation in man is somewhat more complex than in animal models, but the role of the microbiota and of interventions that modulate the microbiome, though not yet ready for clinical practice, continue to be fertile areas for basic and clinical research.
Keywords: microbiome; microbiota; nonalcoholic fatty liver disease; nonalcoholic steatosis; choline; alcohol; gut permeability